1H NMR‐based metabonomic evaluation of the pesticides camptothecin and matrine against larvae of Spodoptera litura. Issue 1 (12th August 2020) - Dai, Li‐shang; Tian, Hui‐fei; Hang, Yang; Wen, Chao‐wei; Huang, Ying‐hao; Wang, Bin‐feng; Hu, Jing‐wei; Xu, Jia‐ping; Deng, Ming‐jie
Abstract: BACKGROUND: Camptothecin (CPT) and matrine (MAT) have potential as botanical pesticides against several pest species. However, the mechanisms of metabolic and physiological changes in pests induced by CPT and MAT are unknown. In this study, a toxicological test, an NMR‐based metabolomic study, an enzymatic test, and an RT quantitative PCR (RT‐qPCR) experiment were all conducted to examine the effect of CPT and MAT on Spodoptera litura . RESULTS: CPT (0.5–1%) exerted high toxicity against larvae of S. litura and caused growth stagnation and high mortality of larvae. A variety of metabolites were significantly influenced by 0.5% CPT, including several energy‐related metabolites such as trehalose, lactate, succinate, citrate, malate, and fumarate. In contrast, MAT showed low toxicity against larvae and induced almost no changes in hemolymph metabolites of S. litura . Enzymatic tests showed that trehalase activity was significantly decreased in larvae after feeding with 0.5% CPT. RT‐qPCR showed that the transcription levels of alanine aminotransferase, malate dehydrogenase, and isocitrate dehydrogenase were decreased while lactate dehydrogenase was increased in the 0.5% CPT‐treated group. CONCLUSIONS: These data indicate that one of the important mechanisms of CPT against S. litura larvae is via the inhibition of trehalose hydrolysis and glycolysis . Our findings also suggest that CPT exhibits a stronger toxicological effect than MAT against S. litura, which provides basic information for the application of CPT in the control of S. litura or other lepidoptera pests. Abstract : CPT exhibits a stronger toxicological effect than MAT against S. litura. CPT against S. litura larvae is via the inhibition of trehalose hydrolysis and glycolysis. © 2020 Society of Chemical Industry